COLLABORATIVE FILE SHARING SYSTEM USING JXTA P2P NETWORKING INFRASTRUCTURE – AN APPLICATION DEVELOPMENT - Kasyful Amron (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
This work aims to develop a simple workflow based collaborative application running over peer to peer network. Basic features of the application are to support communication and coordination in a workflow-based document production. Its offer services for text chat and file sharing. Text chat has two features, group chat or conference and personal chat, while file sharing service supports both synchronous and asynchronous mode that implies a repository function. As this application is developed with the assumption that it will be applied within a close environment, it is complied with a general security mechanism. Design and development processes of this application are depicted in the form of UML diagrams and implemented using Java Programming Language.